2014
DOI: 10.2989/00306525.2014.948943
|View full text |Cite
|
Sign up to set email alerts
|

Research and conservation of the larger parrots of Africa and Madagascar: a review of knowledge gaps and opportunities

Abstract: Supplementary File S1: Questionnaire sent to individuals and organisations involved with parrot research and conservation soliciting information on conservation status and opinions on threats, and priority actions for research and conservation within their area of expertise. Categories for scope, severity and impact of different threats adapted from the IUCN-CMP Unified Classification of Direct Threats version 3.1 THE CONSERVATION STATUS OF AFRICAN PARROTSThis survey is being conducted as part of an initiative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 117 publications
4
62
0
Order By: Relevance
“…One of the group's first tasks has been to evaluate and review the situation concerning the threats facing Psittaciformes in each of several regions. Thus far, and alongside Olah et al (2016) covering the global situation, reviews of Afrotropical (Martin et al 2014) and Neotropical parrots (Berkunsky et al 2017) have been completed. This special issue presents Olah et al's (2018) equivalent review for Oceania (comprising Australia, New Zealand, and the islands of the Pacific and Wallacea).…”
Section: The Most Threatened Bird Ordermentioning
confidence: 99%
See 1 more Smart Citation
“…One of the group's first tasks has been to evaluate and review the situation concerning the threats facing Psittaciformes in each of several regions. Thus far, and alongside Olah et al (2016) covering the global situation, reviews of Afrotropical (Martin et al 2014) and Neotropical parrots (Berkunsky et al 2017) have been completed. This special issue presents Olah et al's (2018) equivalent review for Oceania (comprising Australia, New Zealand, and the islands of the Pacific and Wallacea).…”
Section: The Most Threatened Bird Ordermentioning
confidence: 99%
“…The three regional reviews have identified much consistency in the threats faced by parrots together with some important differences (see below), as well as the poor state of ecological knowledge of many species. For example, many parrot species in Africa and Madagascar are known to be declining, yet at present there are major knowledge gaps hindering conservation action, the most recent conservation gains being made in southern Africa (Martin et al 2014). The review of threats faced by Neotropical parrots (Berkunsky et al 2017) followed a population-based approach and reported the scope of threats affecting 192 populations of 96 species of Neotropical parrots across 21 countries.…”
Section: The Most Threatened Bird Ordermentioning
confidence: 99%
“…It has been suggested that the Cape Parrot is under tremendous pressure, not only due to habitat fragmentation, but also due to the illegal harvesting of wild birds and eggs for the pet trade (Wirminghaus et al, 1999; Martin et al, 2014). The Cape Parrot is currently still observed as a subspecies of P. robustus and it was therefore not classified by the International Union for Conservation of Nature (IUCN) or CITES as endangered or threatened.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Newton (2007) revealed that the scarcity of nests can influence the densities of breeding pairs of birds in natural cavities. This shortage of nest can limit the physical size of the breeding population of birds as described by Beissinger and Bucher, (1992); Martin et al, (2014).…”
Section: Nests Density and Tree Species Used By The Grey Parrotmentioning
confidence: 99%
“…Nevertheless, the destruction of habitats of the Grey Parrot is today the greatest threat to the survival of the species in the range states (Martin et al, 2014;Olah et al, 2016). Habitat encroachment and fragmentation by humans often has subtle and far-reaching effects that are not readily apparent at the beginning.…”
Section: Introductionmentioning
confidence: 99%